2017
DOI: 10.1371/journal.pone.0179672
|View full text |Cite
|
Sign up to set email alerts
|

Dicumarol inhibits PDK1 and targets multiple malignant behaviors of ovarian cancer cells

Abstract: Pyruvate dehydrogenase kinase 1 (PDK1) is overexpressed in ovarian cancer and thus is a promising anticancer therapeutic target. Our previous work suggests that coumarin compounds are potential inhibitors of PDKs. In this study, we used the ovarian cancer cell line SKOV3 as the model system and examined whether dicumarol (DIC), a coumarin compound, could inhibit ovarian cancer through targeting PDK1. We showed that DIC potently inhibited the kinase activity of PDK1, shifted the glucose metabolism from aerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…They possess complementary and overlapping mechanisms to slow down the carcinogenic process by scavenging free radicals (Lee et al, 2013), suppressing survival and proliferation of malignant cells (Yan et al, 2018), as well as diminishing invasiveness and angiogenesis of tumors (Lu et al, 2018a). They exert wide and complex range of actions on different molecular targets and signal transduction pathways including membrane receptors (Deng et al, 2017), kinases (Dou et al, 2018), downstream tumor-activator or -suppressor proteins (Adams et al, 2010), transcriptional factors (Zhang et al, 2017b), microRNAs (miRNAs) (Cojocneanu et al, 2015), cyclins, and caspases (Yan et al, 2018).…”
Section: Phytochemicals With Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They possess complementary and overlapping mechanisms to slow down the carcinogenic process by scavenging free radicals (Lee et al, 2013), suppressing survival and proliferation of malignant cells (Yan et al, 2018), as well as diminishing invasiveness and angiogenesis of tumors (Lu et al, 2018a). They exert wide and complex range of actions on different molecular targets and signal transduction pathways including membrane receptors (Deng et al, 2017), kinases (Dou et al, 2018), downstream tumor-activator or -suppressor proteins (Adams et al, 2010), transcriptional factors (Zhang et al, 2017b), microRNAs (miRNAs) (Cojocneanu et al, 2015), cyclins, and caspases (Yan et al, 2018).…”
Section: Phytochemicals With Anticancer Propertiesmentioning
confidence: 99%
“…Dicumarol (DIC) is the natural anticoagulant derived from coumarin, by bacterial action in spoiled sweet clover hay (Melilotus officinalis, Fabaceae). In BALB/c nude mouse xenograft model, DIC (30 mg/kg) significantly suppressed the growth of SKOV3 ovarian carcinoma cells (Zhang et al, 2017b). The in vitro molecular mechanistic studies suggested that DIC STAT3 and associated protein (Zhu et al, 2016;Odeh et al, 2018) Ursolic acid (triterpenoids) Oldenlandia diffusa (Rubiaceae)…”
Section: Phytochemicals In Pre-clinical Trialsmentioning
confidence: 99%
“…PDK1 is also highly expressed in chemoresistant ovarian cancer cells [ 63 ]. Dicumarol could inhibit PDK1 activity, shifting the glucose metabolism from aerobic glycolysis to OXPHOS, increasing ROS levels, and inducing apoptosis in vitro and in vivo in ovarian cancer [ 64 ].…”
Section: Ovarian Cancer Metabolismmentioning
confidence: 99%
“…PDK1 was overexpressed in the highly glycolytic human ovarian cancer cell line OC316 compared with the less glycolytic cell line IGROV-1 21 . Dicumarol, a coumarin compound, has been found to inhibit PDK1 and suppress ovarian cancer tumor growth in vivo 22 . A recent study demonstrated PDK1 contributes to cisplatin resistance of ovarian cancer through EGFR activation and promotes epithelial-mesenchymal transition 23 .…”
Section: Introductionmentioning
confidence: 99%